IMPLEMENTATION OF LOCAL WISDOM PROJECT BASED LEARNING IN ELEMENTARY SCHOOLS - Anggraini Hamzah; Nasution Nasution; Roni Rodiyana (Universitas Majalengka, 2025)
Project-based learning based on local wisdom is increasingly important in education in Indonesia. Through project-based learning, students are invited to actively participate in activities that are relevant to culture and the environment that can foster a sense of love for their region. This type of research is included in the type of field research, the research design used is a qualitative descriptive method. The techniques used to collect the data needed in the study were interviews, observations, and documentation. Based on the research results, it is known that students really enjoy doing project-based learning which is carried out through making kupang omelettes. Apart from having fun learning, students also know and love the local wisdom of their own region, one of which is typical Kupang food which is a typical Sidoarjo food. The project learning activity was carried out by making mussel omelettes using ready-to-process dry mussels as the basic ingredient. This activity can increase local wisdom through learning in elementary schools with fun project learning, so that it can increase the feeling of love for the country and of course student learning outcomes, especially science and social studies lessons.